Investigation of Viral, Bacterial and Parasitic Zoonotic Diseases in Rodents in Turkey - Mehmet Ozkan Timurkan; Esin Guven; Seyda Cengiz; Hakan Aydın; Ridvan Kirman; Hamza Avcioglu (Veterinary Medicine and Science)
ABSTRACT Background Rodents are reservoir hosts for zoonotic pathogens that cause tropical diseases, many of which have been overlooked. Objectives The aim of this study was to investigate the presence of viral lymphocytic choriomeningitis and hantavirus infections, bacterial tularaemia and leptospirosis, and parasitic leishmaniasis and toxoplasmosis in rodents that are likely to carry and spread zoonotic agents, by using molecular methods. Methods A total of 498 voles collected from 20 counties of Erzurum province. Conventional PCR was used for pathogen search. PCR‐positive samples were subjected to sequence analysis. Results Hantavirus (4.8%, 24/498) and tularaemia (0.8%, 4/498) positivity were detected. However, no positivity was detected for other selected pathogens. Conclusions Rodents, which are pathogen carriers and potential risk factors, are thought to may act as reservoirs for hantavirus and tularaemia in the study area. A preliminary study has been carried out at the point of detection of these diseases of global importance. The extent of the distribution of the infections, alternative hosts and the consequences of human exposure needs to be clarified through further studies.